1980
DOI: 10.1002/cyto.990010302
|View full text |Cite
|
Sign up to set email alerts
|

Percentage of cells in the S phase of the cell cycle in human lymphoma determined by flow cytometry. Correlation with labeling index and patient survival

Abstract: The percentage of cells with S phase DNA content (S cells) was determined by flow cytometry in cell suspensions obtained from 27 patients with non-Hodgkin's lymphomas. DNA was measured in ethanol-fixed cells stained with propidium iodide after RNase treatment. Cells from 17 samples were also exposed to [3H]-thymidine and labeling indices were determined. An excellent linear correlation was observed between the percentage of S cells calculated by flow cytometry and the labeling index (I' = 0.95). To determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
0

Year Published

1982
1982
1995
1995

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…In our study, however, it appears that DAPI staining may be partially responsible since the same samples stained with PI showed lower S-fractions. Previous flow cytoinetric studies using unfixed cells suggested that the size of the S-fraction in non-Hodgkin's lymphomas correlates with patient survival (4,16). These were prospective studies with relatively short clinical follow-up.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our study, however, it appears that DAPI staining may be partially responsible since the same samples stained with PI showed lower S-fractions. Previous flow cytoinetric studies using unfixed cells suggested that the size of the S-fraction in non-Hodgkin's lymphomas correlates with patient survival (4,16). These were prospective studies with relatively short clinical follow-up.…”
Section: Discussionmentioning
confidence: 96%
“…This differ--Cellular DNA content in human lymphoma cells has been analyzed extensively using flow cytometry (FCM). These studies have been performed primarily on cell suspensions obtained from unfixed tissues (3,4,(7)(8)(9)(16)(17)(18) and have provided information on ploidy changes and cell kinetic properties which are valuable in the detection and classification of lymphoid tumors. Recently, flow cytometric analyses of DNA content in cells from formalin-fixed, paraffin-embedded tissues have been successfully performed (2,6,(10)(11)(12)151.…”
mentioning
confidence: 99%
“…The proliferation indices, as defined by flow cytometric and autoradiographic methods, have shown their relevance as prognostic indicators in NHLs (Braylan et al, 1980;Brandt et al, 1981;Costa et al, 1981;Scarffe & Crowther 1981;Kvaloj et al, 1985;Roos et al, 1985;Christensson et al, 1986;Lenner et al, 1987;Griffin et al, 1988;Silvestrini et al, 1989;Grierson et al, 1990;Rehn et al, 1990;Joensuu et al, 1990) as well as in other human malignancies (Volm et al, 1985;Volm et al, 1988;Costa et al, 1990;McGuire et al, 1990;O'Reilly et al, 1990;Silvestrini et al, 1990). However, cell kinetic variables have been usually studied independently on different series of patients, thus preventing a clear comparison between the different methods.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the flow cytometric Sphase cell fraction (FCM-S) is a discriminant of clinical outcome in NHL patients (Braylan et al, 1980;Scarffe & Crowther, 1981;Roos et al, 1985;Christensson et al, 1986;Lenner et al, 1987;Griffin et al, 1988;Grierson et al, 1990;Rehn et al, 1990;Joensuu et al, 1990). Flow cytometric analysis is an automatic and quick method to measure the S-phase cell fraction, and an advantage is that stocked paraffin blocks can be used for retrospective analysis.…”
mentioning
confidence: 99%
“…Thus it is important to search for a rapid and reproducible indicator of potential proliferative activity as an alternative to LI. Several recent papers have suggested that the S phase fraction, evaluated by flow cytometry, meets these requisites (1)(2)(3)(4)12,13,27,29,30). With the present study we proposed to compare the prognostic relevance of LI and S-fraction on the same series of patients with NHL.…”
mentioning
confidence: 99%